Garlic oil-loaded nanodisks for the amelioration of acute lung injury via modulation of the NF-κB and Keap1–Nrf2 axis - Hou, Ruilin; Jiang, Bowen; Wang, Kai; Yang, Xiaoying; Zhang, Wenping (Frontiers in Molecular Biosciences, 2026)
BackgroundAcute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are prevalent and severe respiratory conditions with high morbidity and mortality rates, and specific treatment modalities are lacking. Garlic oil (GO), which is rich in sulfur compounds, has diverse biological properties, including anti-inflammatory and antioxidant effects; nonetheless, its utility is hindered by its limited water solubility and bioavailability. Nanotechnology-based formulations offer a promising solution to enhance GO efficacy. The aim of this investigation was to elucidate the protective effect and underlying mechanism of GO nanodisks (GO-nanodisks) on lipopolysaccharide (LPS)-induced acute lung injury.MethodsWe developed a novel prescription utilizing GO-nanodisks. An acute lung injury model was induced in mice through LPS administration. The mice were randomly allocated into groups: healthy untreated, positive control, GO (50 mg/kg), and GO-nanodisks (50 mg/kg). Tail vein injections were administered accordingly. Subsequent assessments included lung histopathology; inflammatory cytokine (TNF-α, IL-6, IL-4, and IL-10) levels; oxidative stress marker (MDA, SOD, T-AOC, NO, and CAT) levels; and protein expression analyses.ResultsThis study successfully developed GO-nanodisks using a novel fabrication method. The GO-nanodisks demonstrated favorable physicochemical characteristics, with a mean particle diameter of 148 ± 3 nm, a polydispersity index (PDI) of 0.15 ± 0.02, a zeta potential of −0.2 ± 0.1 mV, and an encapsulation efficiency of 55.26% ± 0.04%. Compared with the positive control group, the GO-nanodisk group presented significantly reduced lung tissue pathology, lower inflammatory factor levels, and an improved oxidative stress status. Furthermore, the GO-nanodisk group displayed Keap1/Nrf2 signaling pathway activation and NF-kappa B pathway inhibition, surpassing the efficacy of the GO group.ConclusionThe results of this study demonstrate that the nanodisks formulation developed in this work effectively enables stable encapsulation of GO, enhances its bioavailability, and improves its protective efficacy against LPS-induced ALI. Furthermore, this formulation provides a promising theoretical foundation for the encapsulation of oil-based pharmaceuticals.